Implementasi Administrasi Pemerintahan Desa Di Desa Pineleng Satu Timur Kecamatan Pineleng Kabupaten Minahasa - Kalesaran, Renaldy Jimmy; Mandagi, Martinus; Tumbel, Gionpeace (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The Central Government through Law No. 23 of 2014 gives authority to regional governments to carry out regional government affairs according to the principle of autonomy and co-administration with the principle of broadest autonomy within the system and principles of the Unitary State of the Republic of Indonesia. The implementation of village government administration is carried out through orderly recording of data and information in village register books and the development of village register books needed in carrying out reports according to statutory provisions. The importance of fostering village administration implementation is because without administration it is impossible for an organizational activity to be carried out. In managing village administration that is good and right, it will create an orderly administration, namely being able to provide data and information that is easy for the community and for the village government in making policies and authority in the village. Policy implementation is a legal administration tool, where various actors, organizations, procedures and techniques work together to implement policies to achieve the desired impact and goals. Seeing that the administration implementation in Pineleng Satu Timur Village is still far below the standard, the researchers considered that it was necessary to carry out various strategies or ways to improve the implementation of administrative activities so that in the end a system that was organized and could be managed optimally was realized.